Konsep Tauhid Imam Al-Ghazali Tentang Mekanisme Pasar Dalam Islam - Ita Marianingsih; Lian Fawahan (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The market is an element of natural harmony, the market has a very important role in the economy. Al Ghazali views the market mechanism as evolving as a natural component. Al-Ghazalis rationale about the market mechanism, namely from demand and supply, according to Al-Ghazali, demand and supply occur under the power of Allah. This study uses a qualitative descriptive study using literature quoted from relevant book journals and websites. The purpose of this study is that humans will involve God in any activity without exception in the market because the market is not only a means for buying and selling but also a place for worship. This concept of monotheism has an important role in the market because monotheism teaches that God is one. And with this concept of monotheism, big profits are not a top priority for market participants because they will be more concerned with the afterlife than the world. If every human being has a strong faith, an Islamic market mechanism will be created and a fair market will also be created so that it will prosper human life. Keywords: Al-Ghazali, Market Mechanism, Tauhid